A multilevel thrust filtration defending mechanism against DDoS attacks in cloud computing environment. (1st January 2014) - Iyengar, N.Ch. Sriman Narayana; Ganapathy, Gopinath; Mogan Kumar, P.C.; Abraham, Ajith
Cloud computing is a technology which not only gained advantages from ascendant technologies, but also suffered from its security breaches, of which availability is the most serious security issue. Distributed Denial of Service (DDoS) is a kind of resource-availabilityrelated attack launched with the aim of subverting the Data Centre (DC) for resource unavailability to the legitimate clients. In this paper, we propose 'Multilevel Thrust Filtration (MTF) mechanism' as a solution, which authenticates the incoming requesters and detects the different types of DDoS attacks at different levels to detect the most intensive attack at an early stage to prevent the unnecessary traffic reaching the DC. A hybrid solution is proposed to detect four different kinds of attacks that have been taken into consideration. Profit analysis proved that the proposed mechanism is deployable at an attack-prone DC for resource protection, which would eventually result in beneficial service at slenderised revenue.